Persistence of Cardiac Remodeling in Preadolescents With Fetal Growth Restriction. (January 2017) - Sarvari, Sebastian Imre; Rodriguez-Lopez, Merida; Nuñez-Garcia, Marta; Sitges, Marta; Sepulveda-Martinez, Alvaro; Camara, Oscar; Butakoff, Constantine; Gratacos, Eduard; Bijnens, Bart; Crispi, Fatima
Abstract : Background—: Fetal growth restriction (FGR) affects 5% to 10% of newborns and is associated with increased cardiovascular mortality in adulthood. We evaluated whether prenatal cardiovascular changes previously demonstrated in FGR persist into preadolescence. Methods and Results—: A cohort study of 58 FGR (defined as birth weight below 10th centile) and 94 normally grown fetuses identified in utero and followed-up into preadolescence (8–12 years of age) by echocardiography and 3-dimensional shape computational analysis. Compared with controls, FGR preadolescents had a different cardiac shape, with more spherical and smaller hearts. Left ventricular ejection fraction was similar among groups, whereas FGR had decreased longitudinal motion (decreased mitral annular systolic peak velocities: control median, 0.11 m/s [interquartile range, 0.09–0.12] versus FGR median 0.09 m/s [interquartile range, 0.09–0.10]; P <0.01) and impaired relaxation (isovolumic relaxation time: control, 0.21 ms [interquartile range, 0.12–0.35] versus FGR, 0.35 ms [interquartile range, 0.20–0.46]; P =0.04). Global longitudinal strain was decreased (control mean, −22.4% [SD, 1.37] versus FGR mean, −21.5% [SD, 1.16]; P <0.001) compensated by an increased circumferential strain and with a higher prevalence of postsystolic shortening in FGR as compared with controls. These differences persisted after adjustment for parental ethnicity and smoking, prenatal glucocorticoid administration, preeclampsia, gestational age at delivery, days in intensive care unit, sex, age, and body surface area at evaluation. Conclusions—: This study provides evidence that cardiac remodeling induced by FGR persists until preadolescence with findings similar to those reported in their prenatal life and childhood. The findings support the hypothesis of primary cardiac programming in FGR for explaining the association between low birth weight and cardiovascular risk in adulthood. Abstract : Supplemental Digital Content is available in the text.